Step into Hydrogen- and Carbon Power Engineering - N. S. Nasarov (Наука и техника)
Well-known and mid-19-th century widely spread methods of converting solid fuel being considered as ‘‘inconvenient” for usage into so called “universal” gaseous fuel have become non- profitable due to emergence oi cheap natural gas.The paper contains a proposal to reanimate old and half-forgotten gasification methods on the basis of new and higher technological level, namely: continuous decomposition of high temperature water steam by solid fuel carbon with production of gas-generator gas consisting basically of two fuel gases - hydrogen and carbon monoxide (HCM).